Solve the simultaneous equation by Cramer’s rule 6x – 4y = -12 , 8x – 3y = -2 ​

Question

Solve the simultaneous equation by Cramer’s rule 6x – 4y = -12 , 8x – 3y = -2

in progress 0
Piper 4 weeks 2021-11-02T07:09:35+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-02T07:11:25+00:00

    6x – 4y = -12

    8x – 3y = -2

    D = | 6 -4 |. D = (-18 +32) = 14

    | 8 -3 |

    Dx = | -12 -4 |. Dx = (36 – 8) = 28

    | -2 -3 |

    Dy = | 6 -12 |. Dy = (-12 + 96) = 84

    | 8 -2. |

    X = (Dx/D) = (28/14) = 2

    Y = (Dy/D) = (84/14) = 6

    so, X = 2 and Y = 6

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )